Effect of Pink Perch Gelatin on Physiochemical, Textural, Sensory, and Storage Characteristics of Ready-to-Cook Low-Fat Chicken Meatballs - Khushboo; Nutan Kaushik; Kristina Norne Widell; Rasa Slizyte; Asha Kumari (Foods, 2023)
In recent years consumer demand for low-fat convenience food is increasing rapidly. This study was designed to develop low-fat ready-to-cook (RTC) chicken meatballs using pink perch gelatin. Meatballs were prepared using different concentrations of fish gelatin (3%, 4%, 5%, and 6%). The effect of fish gelatin content on the physico-chemical, textural, cooking, and sensory properties of meatballs was studied. Further, the shelf-life of meatballs was also studied at 4 °C for 15 days and −18 °C for 60 days. The addition of fish gelatin to meatballs decreased the fat content by 67.2% and 79.7% and increased the protein content by 20.1% and 66.4% in comparison to control and Branded Meatballs, respectively. As compared to the Control Meatballs, the addition of fish gelatin also reduced hardness by 26.4% and increased yield and moisture retention in the RTC meatballs by 15.4% and 20.9%, respectively. Sensory analysis suggested that a 5% fish gelatin addition in meatballs has the best acceptability among all tested treatments. Storage study indicated that the addition of fish gelatin to RTC meatballs delayed lipid oxidation during both refrigerated and frozen storage. The results suggested that pink perch gelatin can be used as a fat replacer in chicken meatballs and can potentially increase their shelf-life.